Four-Rod Stabilization of Severely Destabilized Lumbar Spine Caused by Metastatic Tumor. (30th May 2013) - Shibuya, Isao; Sairyo, Koichi; Kanamori, Yasuo; Dezawa, Akira
Abstract : We report a case of a 67-year-old female with severely destabilized lumbar spine caused by metastatic malignant tumor. The primary lesion was a thyroid follicular adenocarcinoma. Complete destruction of the L3, L4, and L5 vertebrae had resulted in severe instability, which left the patient with severe back pain and bed-ridden. Since the vertebrae were so severely damaged at 3 levels, 4 rods were used to stabilize the spine. Following stabilization, the pain was alleviated and the patient's quality of life improved. We introduce here the 4-rod technique to stabilize the spine over 3 vertebral levels following severe destruction by metastatic tumor.